Does the reform of the phased reduction of the pension insurance contribution rate benefit the labor income share of enterprises? - Dou, Chengqiang; Liu, Ying (Frontiers in Public Health, 2025)
IntroductionThis paper develops a theoretical model to clarify the mechanisms by which pension insurance contribution rate affects the labor income share of enterprises and conducts empirical validation.MethodsUtilizing a difference-in-differences approach, this paper analyzes data from China’s A-share listed companies from 2013 to 2018 to examine the impact and mechanism of the phased reduction of the pension insurance contribution rate on enterprise labor income share.Results and discussionThe phased reduction of the pension insurance contribution rate is beneficial for increasing enterprise labor income shares, with significant variations observed across regions and enterprise ownership types. The actual pension insurance contribution rate and capital intensity are two potential mechanisms through which this reform affects labor income share.ConclusionIn summary, we establish a causal link between the reform of the phased reduction of the pension insurance contribution rate and enterprise labor income share. This suggests that continuing the reform could increase labor income share, but it necessitates enhanced collection and management of pension insurance contributions, along with differentiated policies based on regional and enterprise ownership characteristics.